Lecturer Learning Media Development Training Through Preparation Socialization Of Learning Tools For Semester Learning Plans (RPS) - Khairunnisah, Noni Antika; Maryanti, Sri; Syahrir, Syahrir; Supriadin, Supriadin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The aimed of this PKM activity is to improve the performance of lecturers through an important understanding of mastering the techniques for preparing learning tools, namely semester learning plans (RPS) to support students' level of understanding in mastering the lectures being conducted. Both in terms of understanding the material for students and the organization of delivering the material according to what is targeted in the learning process in lectures for the lecturers themselves.